2020
DOI: 10.1021/acs.jpca.0c01609
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic Frequencies of (MO)2 and Related Hydrides for M = Mg, Al, Si, P, S, Ca, and Ti and Heuristics for Predicting Anharmonic Corrections of Inorganic Oxides

Abstract: The low-frequency vibrational fundamentals of D 2h inorganic oxides are readily modeled by heuristic scaling factors at fractions of the computational cost compared to explicit anharmonic frequency computations. Oxygen and the other elements in the present study are abundant in geochemical environments and have the potential to aggregate into minerals in planet-forming regions or in the remnants of supernovae. Explicit quartic force field computations at the CCSD­(T)-F12b/cc-pVTZ-F12 level of theory generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 93 publications
(122 reference statements)
5
30
0
Order By: Relevance
“…While experimental values are unavailable to benchmark the c-C 3 HF and c-C 3 HCl molecules directly, their structures and internal coordinate definitions are similar to those of both c-C 3 HCN and the previously studied c-C 3 H 2 , suggesting that the QFF methodology should yield reliable rotational constants for them, too. Similarly, the exceptional performance of the F12-TZ QFF in the rotational constants supports the corresponding vibrational frequencies, which are already expected to be reliable at this level of theory. …”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…While experimental values are unavailable to benchmark the c-C 3 HF and c-C 3 HCl molecules directly, their structures and internal coordinate definitions are similar to those of both c-C 3 HCN and the previously studied c-C 3 H 2 , suggesting that the QFF methodology should yield reliable rotational constants for them, too. Similarly, the exceptional performance of the F12-TZ QFF in the rotational constants supports the corresponding vibrational frequencies, which are already expected to be reliable at this level of theory. …”
Section: Resultssupporting
confidence: 66%
“…QFFs are fourth-order Taylor series expansions of the internuclear potential energy portion of the Watson Hamiltonian . When conjoined to coupled cluster theory at the singles, doubles, and perturbative triples level within the F12b explicitly correlated formalism [CCSD­(T)-F12b] , and a triple-ζ basis set, QFFs can achieve agreement to within 5–7 cm –1 of gas-phase experimental vibrational frequencies. The accuracy of the rotational data is typically less impressive, especially compared to more expensive composite methods, but the availability of experimental rotational data for c-C 3 HCN can serve to benchmark the performance of the QFFs for the other two molecules given the similar structures. Regardless, the fundamental vibrational frequencies provided here will be invaluable in elucidating the spectra gathered by the existing Stratospheric Observatory for Infrared Astronomy (SOFIA) and the upcoming James Webb Space Telescope (JWST).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the anharmonic vibrational frequencies for the related and previously explored OAlOH molecule fall at 12.82 μm (the internal Al-O stretch) or longer directly in this "uncertain area of spectrum" (Mölster et al, 2001) from high-level quantum chemical computations (Fortenberry et al, 2020). This is also in line with (MO) 2 molecules where M Mg, Al, Si, P, S, Ca, and Ti and also where all of the spectral features of these molecules lie below 12 μm with many of these also above 17 μm (Westbrook and Fortenberry, 2020). Similar spectra behavior has also been noted in the enstatite monomer (Valencia et al, 2020).…”
Section: Introductionsupporting
confidence: 61%
“…Then, the SPECTRO program (Gaw et al, 1991) utilizes rotational and vibrational perturbation theory at second-order (VPT2) to produce the rotational constants and the fundamental vibrational frequencies (Mills, 1972;Watson, 1977;Papousek and Aliev, 1982). SPECTRO can not only treat Fermi resonances, but polyads of these resonances for more accurate descriptions of the frequencies (Martin and Taylor, 1997 (Møller and Plesset, 1934;Frisch et al, 2009) and have previously been shown to be reliable for semi-quantitative descriptions of the fundamental intensities (Yu et al, 2015;Finney et al, 2016;Westbrook and Fortenberry, 2020). These are also reported for the molecules of interest.…”
Section: Computational Detailsmentioning
confidence: 90%
“…QFFs are fourth-order Taylor series expansions of the internuclear potential energy portion of the Watson Hamiltonian [ 20 ]. When coupled with the F12-TZ level of theory, QFFs frequently offer agreement with gas-phase vibrational frequencies of within 5 to 7 cm [ 21 , 22 , 23 , 24 , 25 ]. Other techniques for computing accurate anharmonic spectral data exist [ 26 ], but as a result of the good performance of the F12-TZ QFF on ammonia borane, this same methodology is used herein to investigate water borane (BH OH ), borinic acid (BH OH), HBO, and borane (BH ).…”
Section: Introductionmentioning
confidence: 99%